Pengaruh Fasilitas Perpajakan, Profitabilitas, Leverage dan Struktur Modal Terhadap Manajemen Pajak - Elia Rossa; Achmad Zauhar Muqtafi; Afifah Rohmawati; Alisya Athalia; Alya Syafikah Rani; Anissa Pujiwaty; Yuyun Yuyun (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This study analyzes the impact of key variables such as tax facilities, profitability, leverage, and capital structure on tax management practices in a corporate context. Through literature research, it was found that profitability, leverage, and capital structure play a significant role in managing a company's tax liabilities. However, taxation facilities, while aimed at improving compliance, tend to have a limited impact in tax management practices. This article emphasizes the need for a holistic approach to tax decision making, taking into account a number of these factors simultaneously.